Quality of life in patients with gastroesophageal reflux disease following pharmacotherapeutic, endoscopic, and surgical treatment - Jurkowska, Grażyna; Świdnicka-Siergiejko, Agnieszka; Łagoda, Katarzyna; Sierżantowicz, Regina; Dąbrowski, Andrzej (Medical Studies/Studia Medyczne, 2016)
Gastroesophageal reflux disease (GERD) is associated with bothersome symptoms. Their chronic and recurrent character has a negative impact on the physical and mental status of the patients. Improvement in health-related quality of life (HRQOL) of GERD patients along with decreasing the severity of symptoms remain the main aims of therapy. This paper reviews literature regarding HRQOL in GERD patients, as well as the impact of various treatment modalities on the patient’s status, the incidence and severity of symptoms thereof, and subjective quality of life. Additionally, the factors that may influence the treatment outcome are also discussed. Several studies showed that the improvement of HRQOL is greater after surgical treatment than with pharmacological therapy. However, long-term studies are still needed to determine if surgery can constitute the equivalent of lifelong medical therapy.